Perbandingan Hasil Belajar Dan Daya Juang (Adversity Quotient) Mahasiswa Bidikmisi Dan Non Bidikmisi Fakultas Ekonomi Universitas Negeri Padang - Arlin Ayu Fitria; Annur Fitri Hayati (Jurnal Salingka Nagari, 2023)
This study aims to determine (1) Comparison of learning outcomes for bidikmisi and non-bidikmisi students at the Faculty of Economics, Padang State University. (2) Comparison of the adversity quotient of bidikmisi and non-bidikmisi students at the Faculty of Economics, Universitas Negeri Padang. The data used are primary data and secondary data in the form of questionnaires and documentation. The population in this study were active students of the Faculty of Economics, Universitas Negeri Padang with a sample of 84 people who were determined using a proportional random sampling technique. The analytical method used is quantitative analysis. Hypothesis testing using the Independent sample t-test. The results of this study indicate that there is no significant difference between the learning outcomes of bidikmisi and non-bidikmisi students at the Faculty of Economics, Universitas Negeri Padang. There is a significant difference between the fighting power of bidikmisi and non-bidikmisi students. This is evidenced by the hypothesis testing that was carried out, namely Sig. < Sig α (0.000 < 0.05). This means that bidikmisi students have a higher fighting power than non-bidikmisi students.